Returns to public investments in clean plant centers: A case study of leafroll virus-tested grapevines in support of cost-effective grape production systems. (August 2022) - Li, Jie; Troendle, Jason; Gómez, Miguel I.; Ifft, Jennifer; Golino, Deborah; Fuchs, Marc
Abstract: Viruses and related graft-transmissible pathogens cause diseases that cost the grape industry billions of dollars annually if left uncontrolled. The National Clean Plant Network (NCPN), a USDA Farm Bill program, is an organization of clean plant centers that produce and maintain virus-tested foundation vine stocks and distribute propagation material derived thereof to nurseries and growers to minimize the introduction of viruses and virus-like diseases into the vineyard. Foundation Plant Services (FPS) is the major NCPN-grapes center. We examined the economic impacts of public investments in FPS from 2006 to 2019. By focusing on grapevine leafroll disease, our analyses revealed a benefit-cost ratio ranging from 22:1 to 96:1, with a 5% and a 20% disease infection rates in commercial vineyards, respectively. A welfare analysis was consistent with grape growers and nurseries capturing most (64–98%) of the benefits from adopting clean planting material compared with winemakers and other actors in the downstream wine supply chain system. This study provided new insights into the returns to public investments in a clean plant center and documented strong financial incentives for higher adoption of clean vines derived from virus-tested stocks, while justifying continued support of NCPN centers from public and private sectors.